1985
DOI: 10.1002/cjce.5450630610
|View full text |Cite
|
Sign up to set email alerts
|

Fluidised bed gasification of a metallurgical coke with CO2/N2 Mixtures

Abstract: The gasification of a metallurgical coke with CO2/N2 mixtures in a 0.1 m diameter fluidised bed has been studied over the temperature range 810–1050°C. The rate of gasification was found to be essentially kinetically controlled, with negligible influence of fluidisation parameters below 1000°C. A number of flow models were assessed. The plug flow model was found to be the simplest model which could predict the experimental results, giving similar results to the more complex two‐phase flow model of Davidson and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0
10

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 8 publications
2
5
0
10
Order By: Relevance
“…It was also reported that the presence of CO 2 at high concentrations during oxy‐fuel combustion affects the heat transfer, flame ignition, coal burn out, emissions and ash properties . Comparison of the reactivity of coal/char in air and oxy‐fuel combustion environments under various O 2 /N 2 and O 2 /CO 2 conditions has been studied and a number of factors have been identified to cause the difference . This difference in reactivity is due to the differences in the properties of bulk gases, the lower rate of diffusion of oxygen through CO 2 and the higher specific heat capacity of CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that the presence of CO 2 at high concentrations during oxy‐fuel combustion affects the heat transfer, flame ignition, coal burn out, emissions and ash properties . Comparison of the reactivity of coal/char in air and oxy‐fuel combustion environments under various O 2 /N 2 and O 2 /CO 2 conditions has been studied and a number of factors have been identified to cause the difference . This difference in reactivity is due to the differences in the properties of bulk gases, the lower rate of diffusion of oxygen through CO 2 and the higher specific heat capacity of CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…(3)) during combustion is referred to as ignition, whereas quenching of the CO flame is termed extinction. Linjewile and Agarwal [9] and Biggs and Agarwal [10] investigated the CO/CO 2 product ratio for a single porous char particle, whereas Stubington [11] measured the radial variation of temperature of char particle in a fluidized bed. The phenomenon of fragmentation during gasification of microporous chars was reported by Feng and Bhatia [12], based on experimental investigations, and a theoretical analysis of peripheral fragmentation during char combustion and gasification was presented by Wang and Bhatia [13].…”
Section: Introductionmentioning
confidence: 99%
“…Η παραπάνω διαπίστωση συμφωνεί με την παρατηρούμενη αύξηση του ειδικού ρυθμού εξαερίωσης με την θερμοκρασία και την υψηλή μετατροπή του άνθρακα με την επιμήκυνση του χρόνου αντίδρασης. Οι Stubington, Barrett και Duong [202] μελέτησαν την εξαερίωση μεταλλουργικού κώκ, ενός σχετικά αδρανούς εξανθρακώματος που προέρχονταν από Αυστραλιανό μαύρο άνθρακα, με μίγματα CO2 και Ν 2 σε ρευστοστερεά κλίνη και για θερμοκρασίες 810°C ως 1050°Ο Κάτω από αυτές τις συνθήκες, η αύξηση της θερμοκρασίας από 860°C σε 1050°C, είχε σαν αποτέλεσμα την αύξηση του ρυθμού κατανάλωσης του άνθρακα κατά τέσσερεις φορές περίπου.…”
Section: κεφάλαιο IV εξαερίωση άνθρακα με C0unclassified
“…Οι Standish και Tanjung [206] εκτελώντας πειράματα εξαερίωσης με C0 2 εξσνθρακωμάτων ξύλου, με μέγεθος σωματιδίων 10 mm ως 34 mm, στην θερμοκρασιακή περιοχή 900°C -1100°C διαπίστωσαν ότι ο ρυθμός εξαερίωσης είναι ανάλογος του R 0 (R 0 διάμετρος σωματιδίου). Η σημαντική επίδραση της κοκκομετρίας που παρατηρήθηκε, οφείλεται πιθανότατα στο πολύ μεγαλύτερο μέγεθος σωματιδίων που χρησιμοποιήθηκαν στην εργασία αυτή σε αντίθεση με το [172,180,202,204,[206][207][208][209][210][211] που αφορούν την επίδραση της μερικής πίεσης του C0 2 στην εξαερίωση ανθράκων και εξανθρακωμάτων. Η επίδραση της πίεσης του CO2 στην εξαερίωση άνθρακαδιοξειδίου του άνθρακα έχει μελετηθεί σχεδόν αποκλειστικά για την ισοθερμοκρασιακή εξαερίωση, ενώ, εξ όσων γνωρίζει ο γράφων, δεν υπάρχουν μελέτες για την μη -ισοθερμοκρασιακή εξαερίωση με C0 2 .…”
unclassified
See 1 more Smart Citation